Kinetics of the West Nile virus induced transcripts of selected cytokines and Toll-like receptors in equine peripheral blood mononuclear cells. (December 2016) - Uddin, Muhammad; Suen, Willy; Bosco-Lauth, Angela; Hartwig, Airn-Elizabeth; Hall, Roy; Bowen, Richard; Bielefeldt-Ohmann, Helle
Abstract West Nile virus (WNV) is one of the most common causes of epidemic viral encephalitis in horses worldwide. Peripheral blood mononuclear cells (PBMCs) are amongst the first to encounter the virus following a mosquito bite. This study aimed to elucidate the transcription kinetics of cytokine, Toll-like receptor (TLRs) and TLRs-associated genes following WNV challenge of equine PBMCs. PBMCs were challenged with an Australian strain of WNV (WNVNSW2011 ) and transcriptomes were quantified at 2, 6, 12 and 24 h post-infection (pi) using qRT-PCR. Type I and II interferons (IFNα, β and γ) mRNA transcription increased following WNV exposure, as did the transcripts for IL1α, IL1β, IL6, IL8, and IL22, but with slightly varying kinetics. TLR1, 3, 5, 7-9 transcripts were also upregulated in equine PBMCsin response to WNV challenge, as were those for MyD88, NF-κB, TRAF3, STAT1 and 2, IRF3 and 7, ISG15, as well as SOCS1 and 3 compared to the control cells. Expression of selected genes in the draining lymph node, spleen and brain (medulla oblongata) of experimentally infected horses was also assessed and transcription of most of these genes was also upregulated here. Although qRT-PCR detected higher viral RNA at 24 h pi compared to 6 h pi, the virus did not replicate productively in equine PBMCs. The up-regulation of gene-transcription for selected cytokines, IFNs, TLRs and TLRs-associated molecules suggests their involvement in virus recognition and control of WNV infection in the horse.